1879 Md. Laws 173 - (:unkn) unknown (My University, 1876)
Wild Fowl and Game § 23: The clerk of the Circuit Court for Harford county, and the clerk of the Circuit Court for Cecil county, shall upon the application of any resident of the State of Maryland, being the owner of any sink-box, craft or sneak-boat, such as is allowed by this act to be used and employed in shooting at wild water fowl therefrom; and giving satisfactory evidence to said clerk that the said applicant is a resident of the State of Maryland, and is the bona fide owner of the sink-box, craft, or sneak-boat, grant a license under the seal of his court, to such applicant to gun after and shoot at wild water-fowl from such sink-box or sneak-boat northward of the line named and described in first section of this act from the first day of November in each and every year to the thirty-first day of March next succeeding thereafter in each and every year; provided that such license shall not authorize any person using such sink-box or sneak-boat to gun after or shoot at wild water-fowl therefrom within a less distance than half a mile from any shore in Harford or Cecil County, or southward of the line particularly described in the first section of this act.
Keywords: HUNTING REGULATION